2021
DOI: 10.1136/rapm-2020-102427
|View full text |Cite
|
Sign up to set email alerts
|

The analgesic efficacy of liposomal bupivacaine compared with bupivacaine hydrochloride for the prevention of postoperative pain: a systematic review and meta-analysis with trial sequential analysis

Abstract: Background/ImportanceLiposomal bupivacaine (LB) is a prolonged release formulation of conventional bupivacaine designed for prolonging local or peripheral regional single injection anesthesia. To this day, the benefit of the new substance on relevant end points is discussed controversial.ObjectiveThe objective was to determine whether there is a difference in postoperative pain scores and morphine consumption between patients treated with LB and bupivacaine hydrochloride in a systematic review and meta-analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
46
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 39 publications
4
46
0
1
Order By: Relevance
“…These findings are similar to what was found in three recent reviews and meta-analyses 28–30 on comparing perineural liposomal bupivacaine to standard bupivacaine. All three reviews found that perineural liposomal bupivacaine was associated with statistically but not clinically meaningful differences in pain scores compared with standard bupivacaine.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings are similar to what was found in three recent reviews and meta-analyses 28–30 on comparing perineural liposomal bupivacaine to standard bupivacaine. All three reviews found that perineural liposomal bupivacaine was associated with statistically but not clinically meaningful differences in pain scores compared with standard bupivacaine.…”
Section: Discussionsupporting
confidence: 90%
“…We designed our study to compare perineural liposomal bupivacaine to the adjuvant perineural dexamethasone for use in interscalene nerve blocks and for clinical relevance. Because there have been multiple published studies comparing liposomal bupivacaine to plain bupivacaine [28][29][30] but none to plain bupivacaine with dexamethasone, we felt that a randomized controlled trial comparing perineural liposomal bupivacaine to plain bupivacaine with the adjuvant perineural dexamethasone for interscalene nerve blocks would be clinically relevant for many practitioners. The perineural analgesic efficacy of dexamethasone has already been noted previously, and a survey sent to all members of the Society for Ambulatory Anesthesia (SAMBA; Milwaukee, Wisconsin) noted that for patients receiving nerve block, 85% of respondents discharged patients with long-acting blocks.…”
Section: Discussionmentioning
confidence: 99%
“…The active component bupivacaine 12% is an experimental pain-relieving medication, and is in the form of a capsule in a biological degradable structure. It is designed for surgical infiltration to achieve a long-term post-operative analgesia, reduce opioid consumption and improve post-surgical recovery (47). Bupivacaine is slowly released over several days following injection.…”
Section: Saber-bupivacainementioning
confidence: 99%
“…
Hanns-Christian et al 1 conducted a literature review with the objective of determining whether there is a difference in postoperative pain scores and opioid consumption between patients who received liposomal bupivacaine and patients who received bupivacaine hydrochloride.The authors concluded that the beneficial effect on both postoperative pain scores and opioid consumption was small but not clinically relevant. 1
…”
mentioning
confidence: 99%
“…The authors concluded that the beneficial effect on both postoperative pain scores and opioid consumption was small but not clinically relevant. 1…”
mentioning
confidence: 99%